Emission Spectroscopy of OH Radical in Water-Argon Arc Plasma Jet - Alan Mašláni; Viktor Sember (Journal of Spectroscopy)
Emission spectra of OH radical are studied in the plasma jet generated by a plasma torch with hybrid water-argon stabilization. Plasma jet is located in a chamber with pressures 4 kPa and 10 kPa. In spite of high temperatures of produced plasma, OH spectra are observed in a large area of the jet. OH spectra are used to obtain rotational temperatures from the Boltzmann plots of resolved rotational lines. Due to line-of-sight integration of radiation, interpretation of the temperatures is not straightforward. It seems that excited OH molecules can be formed by various mechanisms, mainly in the outer parts of the jet, where thermal processes are not as dominant as in the hot central region.